Management for Lombok Strait with Traffic Separation Scheme (TSS) and Particularly Sensitive Sea Area (PSSA) to Implement the IMO Regulations - Desi Albert Mamahit,; Raudhotul Aulia,; Priyati Lestari,; Ahmad Hidayat Sutawidjaya,; Sundring Pantja Djati, (Technium Social Sciences Journal, 2020)
The growing field of shipping and the changes in the global military strategy of large countries which of course indirectly affect how well a country acts. As an archipelagic nation, Indonesia has the right to conceptualize a Traffic Separation Scheme to improve navigation safety in the Islands Sea Channel, based on Article 53 (6) of the 1982 United Nations Convention on the Law of the Sea (UNCLOS) 1982 and also based on the IMO General Provisions for Adoption, Appointment and Replacement of the Islands Sea Plate. Traffic Separation Scheme (TSS) is a dividing line between the navigation boundaries of trade ships and the territorial waters of national jurisdictions. The Traffic Separation Scheme (TSS) Scheme is a traffic management route system governed by the International Maritime Organization or IMO. Then we can know that Indonesia has the right and obligation to regulate its own sea. Departing from this, the concept of the Traffic Separation Scheme (TSS) and Particularly Sensitive Sea Area (PSSA) was coined, as an effort of embodiment, a derivation of "lex specialis" International provisions adopted by all sea users in the world. This study uses a qualitative method with an explanatory approach. The procedure used to obtain this information is through literature review. Data analysis in this study uses SWOT analysis (strength, weakness, opportunity and threat) and POAC (planning, organizing, actuating and controlling). The result for this case study, must prepare carefully for the implementation of TSS and PSSA in the Lombok Strait, as a country that has declared itself as the first archipelagic state in the world that has a separation in its narrow sea. Given that the implementation is just counting the days. Indonesia does not need to doubt the benefits of TSS and PSSA itself, because TSS and PSSA become a "win-win solution" for both the user and coastal countries